Anthropological medicine in Heidelberg: A personal viewpoint and some thoughts - Lolas-Stepke, Fernando (2008)
In this paper, the author recalls his years as a student at Heidelberg, Germany, in what has come to been known as the “School of Heidelberg”. The author presents the ideas and significance of Paul Christian, his mentor, and the ideas of thinkers such as Ludolf von Kehrl and Viktor von Weizsäcker. Extensive discussion is dedicated to the meaning of the concept of anthropological medicine and to the intellectual relationship of the author with Paul Christian.